Membangun Jembatan di Atas Jurang: Strategi Inklusi Ekonomi untuk Memperkecil Ketimpangan Sosial di Kawasan Urban - Lilian Martha; Mutiara Tsani (Lembaga Publikasi Ilmiah Nusantara, 2026)
Social inequality in urban areas often triggers sharp economic segregation between the upper class and marginalized communities. This community service program aims to implement economic inclusion strategies through a